The effects of oil price shocks on Turkish business cycle: A Markov switching approach - Vasif Abiyev; Reşat Ceylan; Munise Ilıkkan Özgür (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - The purpose of this study is to investigate the relationship between oil price changes and the output growth in Turkey. Design/methodology/approach - The data were taken from International Financial Statistics databases, consisting of monthly data for the period 1986:01-2014:09. Different univariate Markov-switching regime autoregressive models are specified and estimated. Among them we selected univariate MSIH(3)-AR(2) model for output and extended it to verify if the inclusion of various asymmetric oil price shocks as an exogenous variable improves the ability of the Markov switching model. Four different oil price shocks are considered. Findings - We find that amongvarious oil price shocks, onlynet oil price increases have negative effects on output growth and mitigate the magnitude of thesome recessionary periods in Turkey. However, it doesn't strongly explain the behavior of business cycle in Turkey. Research limitations/implications - Our results suggest that the inclusion of other fundamental financial factors in the bivariate Markov switching modelof aggregate economic activity and oil price changes becomes important to explicitly detect the negative impact of oil price shocks on output in Turkey. Originality/value - Our results support the existence of a negative relationship between oil price increases and output growth mentioned in the literature and empirical studies on Turkey.
Keywords: E32; E44; Q41; 330; business cycle; output; Markov switching regime; oil shocks